Peranan Wanita pada Usaha Pengolahan Ikan Asap dalam Peningkatan Pendapatan Rumah Tangga - Misran Hani; Muarif Leo; Abdul Gafur; Risna Risna (Jurnal Sekretaris dan Administrasi Bisnis, 2025)
In this research, the main problem raised is what is the role of women in the smoked fish processing business in increasing income in Gerak Makmur Village, Sampolawa District, South Buton Regency? This research aims to determine the role of housewives in increasing family income in Gerak Makmur Village. This research uses a qualitative approach. The subjects in this research were seven housewives (grilled fish sellers in Gerak Makmur Village. Data collection in this research was carried out using research instruments in the form of interviews, observation and documentation. The data obtained was analyzed descriptively. Based on the research results , it was concluded that (1) The income of grilled fish business actors in 2023 is quite high, the average income of business actors is IDR 46,216,423 per month or the equivalent of IDR 34,360,000 per year South Buton Regency in 2023 of IDR 394,744 /capita/month then shows the large role of grilled fish business actors in meeting the needs of families. Housewives are mostly the main activity which is carried out entirely with the head of the family and other family members , not just a side activity of a housewife